NAVIGATING THE INTERSECTION OF LAW AND TECHNOLOGY: CHALLENGES AND OPPORTUNITIES IN THE DIGITAL AGE - Singh, Shourie Anand; Vashishtha, Namita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid advancement of technology has significantly transformed the legal landscape, presenting both challenges and opportunities in the digital age. This paper explores the intricate intersection of law and technology, analyzing how emerging innovations such as artificial intelligence, blockchain, and cybersecurity reshape traditional legal frameworks. Key challenges include regulatory gaps, jurisdictional ambiguities, and ethical dilemmas, while opportunities lie in modernizing legal practices, enhancing accessibility, and fostering innovation. The research employs a qualitative methodology, incorporating a thematic analysis of case studies, policy documents, and expert opinions. Findings underscore the necessity of proactive legal frameworks to address technological complexities while leveraging innovation for societal benefit. This study aims to provide actionable insights for policymakers, legal practitioners, and technologists to navigate the evolving digital-legal interface effectively.